2014
DOI: 10.1080/08952841.2014.906873
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Health Correlates of Self-Efficacy in Dementia Family Caregivers

Abstract: This study examined whether self-efficacy for controlling upsetting caregiving thoughts would longitudinally predict mental and physical health as well as utilization of psychotropic medications in help-seeking dementia family caregivers (N = 53). Positive associations were found between self-efficacy and self-reported mental health and physical health subscales of the Short Form Health Questionnaire-12, and negative correlations were found between self-efficacy for controlling upsetting thoughts about caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…Consistent with hypotheses, self-reassurance and self-efficacy for controlling upsetting thoughts were associated with reduced caregiver depression, anxiety, and stress and predicted these outcomes beyond the variance accounted for by the other stressors. This result is consistent with research showing the negative relationship between these resources and mental health concerns (George and Steffen, 2014;Gilbert et al, 2004;Romero-Moreno et al, 2011), as well as the positive relationship between coping resources and caregiver well-being (Lopez et al, 2012). Although the construct of self-efficacy for controlling upsetting thoughts has been extensively studied within the caregiving population (Crellin et al, 2014b), self-reassurance has not.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with hypotheses, self-reassurance and self-efficacy for controlling upsetting thoughts were associated with reduced caregiver depression, anxiety, and stress and predicted these outcomes beyond the variance accounted for by the other stressors. This result is consistent with research showing the negative relationship between these resources and mental health concerns (George and Steffen, 2014;Gilbert et al, 2004;Romero-Moreno et al, 2011), as well as the positive relationship between coping resources and caregiver well-being (Lopez et al, 2012). Although the construct of self-efficacy for controlling upsetting thoughts has been extensively studied within the caregiving population (Crellin et al, 2014b), self-reassurance has not.…”
Section: Discussionsupporting
confidence: 88%
“…The specificity of this construct is important, given research showing differences between self-efficacy for different caregiving domains, and therefore offers more precise targets for interventions (Peñacoba et al, 2008). Higher levels of self-efficacy for controlling upsetting thoughts is related to reduced depression in caregivers (Romero-Moreno et al, 2012;Wang et al, 2016), as well as decreased anxiety (George and Steffen, 2014). Self-efficacy for controlling upsetting thoughts has also been found to partially mediate the relationship between caregiving burden and depression in a longitudinal sample (Grano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these limitations, the results of the present study further sustain the specificity and multidimensionality of the caregiving self-efficacy construct indicating that SE:CT may be the most important efficacy belief for caregivers. Targeting SE for controlling upsetting thoughts in caregiver psychoeducation and counseling may be important not only in terms of preventing depressive symptoms, but also considering that SE:CT has been found to influence caregivers health behaviors, the use of psychotropic medication and their perceived physical health (Rabinowitz et al, 2007;Au et al, 2010;George and Steffen, 2014). Moreover, modifying self-efficacy for controlling negative thinking about the caregiving role can result, through the prevention of caregiver depressive symptoms, in other important health and social outcomes both for the caregivers and the carerecipients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that CSE has moderating effects on physical and psychological health as well as the coping ability of caregivers. 31,32 High CSE is associated with lower caregiver burden, more positive gains such as a sense of purpose, and fewer depressive symptoms and distress. 33,34 When taking care of PWD, CSE seems to act as the caregiver's personal resource that mediates other caregiver outcomes, such as caregiving burden and depression.…”
Section: Effects Of Dyadic Interventions On Pwd and Caregiversmentioning
confidence: 99%
“…CSE plays a significant role in both moderating and mediating effects on the well‐being of caregivers. Studies have demonstrated that CSE has moderating effects on physical and psychological health as well as the coping ability of caregivers . High CSE is associated with lower caregiver burden, more positive gains such as a sense of purpose, and fewer depressive symptoms and distress .…”
Section: Introductionmentioning
confidence: 99%